How to fix copyright - Patry, William (Cambridge University Press CambridgeGB)
Argues for the creation of effective copyright laws fit for their purpose. Suggests that to pass effective laws, legislators must be political scientists, empirically investigating the real-world consequences of how proposed laws will affect the production and distribution of works of authorship, as well as the law's impact on access to those works, on innovation, and on prices.